Organizational trust in Public Educational Institutions - Ledesma Cuadros, Mildred Jénica (2020)
The study had as a general objective, comparative evaluation of the differences that exist in the organizational confidence of teaching staff in public institutions in North Lima. The research focus was quantitative, comparative descriptive non-experimental design; the population of 176 teachers and the sample made up of 128 teachers from educational institutions in North Lima (public, convention and Catholic); the instrument used was a questionnaire, structured by 36 reagents, on the Likert scale; which allowed us to describe the organizational confidence in teachers. Among the main conclusions, it was demonstrated that there are differences in the comparative evaluation of the organizational confidence of teaching staff in educational institutions in North Lima; Nevertheless; these significant differences, although they are evident in the variable and dimensions, one of them (dimension of respect), does not present a difference.